FAKTOR-FAKTOR DALAM GLOBALISASI DAN PEMBANGUNAN - Nurharpani Nurharpani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The COVID-19 pandemic has created the need and need to maintain social distance in social interactions (social distancing), quarantine, and isolation so that every vulnerable individual will not be exposed to the virus. The use of technology with online meetings for students and educators is very important, especially in the development of civic education, in order to love the Republic of Indonesia. This paper will discuss the concept and direction of civic education and the urgency of strengthening the concept and direction of progressive citizenship education online in the midst of the covid-19 virus pandemic. The method used in this research is descriptive analytical with a qualitative approach. The results show, First, the concept of Citizenship Education supports the objectives of civic education, which can be interpreted as a subject that focuses on the formation of citizens who have intellectual skills, skills to participate in every civic activity and have a strong civic character so as to make citizens who are intelligent and have character. . Second, the urgency of strengthening the concept and direction of progressive citizenship education online in the midst of the covid-19 virus pandemic prepares students to become good citizens who master knowledge derived from multidisciplinary concepts and theories, practice values, and apply the skills they need to participate. in online education.